2021
DOI: 10.1186/s12929-021-00738-2
|View full text |Cite
|
Sign up to set email alerts
|

USP9X promotes apoptosis in cholangiocarcinoma by modulation expression of KIF1Bβ via deubiquitinating EGLN3

Abstract: Background Cholangiocarcinoma represents the second most common primary liver malignancy. The incidence rate has constantly increased over the last decades. Cholangiocarcinoma silent nature limits early diagnosis and prevents efficient treatment. Methods Immunoblotting and immunohistochemistry were used to assess the expression profiling of USP9X and EGLN3 in cholangiocarcinoma patients. ShRNA was used to silence gene expression. Cell apoptosis, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…In mouse ovary, Usp9x is enriched in the GCs of primordial and primary follicles, which indicates that Usp9x is related to mammalian folliculogenesis (Sato et al, 2004). Herein, we demonstrated that USP9X is an antiapoptotic posttranslational modifier, which inhibits the (Chen et al, 2021;Vucic et al, 2011). Multiple components such as c-FLIP and ASK1 in the death receptor pathway, and MCL-1 of the mitochondrial pathway are direct substrates for DUB USP9X (Kim et al, 2019;Lai et al, 2021;Nagai et al, 2009;Schwickart et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In mouse ovary, Usp9x is enriched in the GCs of primordial and primary follicles, which indicates that Usp9x is related to mammalian folliculogenesis (Sato et al, 2004). Herein, we demonstrated that USP9X is an antiapoptotic posttranslational modifier, which inhibits the (Chen et al, 2021;Vucic et al, 2011). Multiple components such as c-FLIP and ASK1 in the death receptor pathway, and MCL-1 of the mitochondrial pathway are direct substrates for DUB USP9X (Kim et al, 2019;Lai et al, 2021;Nagai et al, 2009;Schwickart et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…Multiple components such as c‐FLIP and ASK1 in the death receptor pathway, and MCL‐1 of the mitochondrial pathway are direct substrates for DUB USP9X (Kim et al, 2019; Lai et al, 2021; Nagai et al, 2009; Schwickart et al, 2010). Additionally, USP9X has an indirect impact on cell apoptosis via the cell death signaling pathways: for example, USP9X induces apoptosis in cholangiocarcinoma cells by increasing the expression of cleaved‐caspase3, a common effector of both the death receptor and the mitochondrial pathways through deubiquitination and preventing the degradation of EGLN3 (Chen et al, 2021). In summary, our study demonstrates for the first time that USP9X is essential for GC function and follicular development in female mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we found that the physical association of USP9X with centrosomes was dependent on the cell cycle and mainly occurred in the S and G2 phases in breast cancer 32 . Another study showed that USP9X plays an anticancer role by stabilizing EGLN3, whose overexpression can arrest cancer cells in the G1 phase and mediate cell apoptosis 49 . In human neural progenitor cell lines, USP9X was found to stabilize RAPTOR protein levels and loss of USP9X resulted in cell cycle arrest in the G0 phase and decreased mTORC1 signaling, which is a major regulator of G0/G1 cell cycle progression 50 .…”
Section: Discussionmentioning
confidence: 96%
“…USP9X was reported to be an oncogene that promotes tumorigenesis and chemoresistance by regulating tumor cell apoptosis [26] and participating in the activation of TCR signaling. USP9x was found to be indispensable for lymphocyte activation, either by controlling ZAP70 ubiquitination or modulating the carma1-bcl10-malt1 complex, but the molecular mechanisms are not clear [ 12 14 ] .…”
Section: Discussionmentioning
confidence: 99%